Effect of Teachers’ Attitude Towards Students with Dyslexia Learning in Public and Private Secondary Schools in Benin City - O Osunde, Yvonne (2025)
This study investigated the effect of teachers’ attitudes on the learning of students with dyslexia in public and private secondary schools in Benin City, Edo State. A descriptive survey research design was adopted, involving 120 teachers (60 from public schools and 60 from private schools) selected through stratified random sampling. Data were collected using the Teachers’ Attitude and Dyslexia Questionnaire (TADQ) with a reliability coefficient of .82. Descriptive statistics, independent samples t-test, and linear regression were employed for data analysis. Findings revealed that teachers’ overall attitudes toward students with dyslexia were moderate (M = 3.12, SD = 0.54), with private school teachers exhibiting more positive attitudes (M = 3.34, SD = 0.48) compared to public school teachers (M = 2.90, SD = 0.59). The independent t-test showed a significant difference between the two groups, t(118) = 4.21, p < .01. Regression analysis further indicated that teachers’ attitudes significantly predicted students’ learning outcomes, F(1, 118) = 32.13, p < .001, accounting for 21% of the variance (β = .46, p < .001). The study concludes that teachers’ attitudes substantially influence the learning experiences of dyslexic students, with systemic disparities between public and private schools shaping these perceptions. It is recommended that regular teacher training, policy interventions, resource provision, and awareness campaigns be prioritized to promote inclusive education and reduce stigma surrounding dyslexia in Nigeria.